A DISCURSIVE LOOK AT THE BOOK COVERS: the dialogues between images and words in Dom Casmurro - Silveira Andretta, Pedro Ivo; Gaspar, Nadea Regina [UNESP] (Univ Fed Paraiba Ccsa, 2012)
This research aims to understand the verbal-visual languages present in a collection of book covers of a narrative romance and the way they portray the contents of the work, with a view to the process of literary text analysis. We resort to the archaeological theory of Michel Foucault in his concepts of statement and discursive formation in the book The Archaeology of Knowledge, which were applied in the work Dom Casmurro by Machado de Assis. It is shown as a result that two statements that serve as themes: The city of Rio de Janeiro in the nineteenth century and female betrayal and adultery, which constituted the discursive formation: The female betrayal and adultery in Rio de Janeiro in the nineteenth century. At the end we found that the theory could help in the discursive practice of literary analysis of narrative texts, opening a possibility of further studies, among the existing ones, also in the field of Information Science.
Keywords: Information Science; Discourse analysis; Brazilian literature; Dom Casmurro; Book Covers